Supramolecular Chemistry in the 3rd Millennium - Housecroft, Catherine (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue is one of the first for the new MDPI flagship journal Chemistry (ISSN 2624-8549) which has a broad remit for publishing original research in all areas of chemistry. The theme of this issue is Supramolecular Chemistry in the 3rd Millennium and I am sure that this topic will attract many exciting contributions. We chose this topic because it encompasses the unity of contemporary pluridisciplinary science, in which organic, inorganic, physical and theoretical chemists work together with molecular biologists and physicists to develop a systems-level understanding of molecular interactions. The description of supramolecular chemistry as 'chemistry beyond the molecule' (Jean-Marie Lehn, Nobel Lecture and Gautam R. Desiraju, Nature, 2001, 412, 397) addresses the wide variety of weak, non-covalent interactions that are the basis for the assembly of supramolecular architectures, molecular receptors and molecular recognition, programed molecular systems, dynamic combinatorial libraries, coordination networks and functional supramolecular materials. We welcome submissions from all disciplines involved in this exciting and evolving area of science.